ANALYSIS OF MARKETING OF INDEPENDENT FARMERS' FRUIT FRUIT IN DOLOK MERAWAN VILLAGE DOLOK MERAWAN DISTRICT, SERDANG BEDAGAI REGENCY - Winni Rachel joys Situmeang; Delyana R Pulungan; Tifany Zia Aznur (RADJA PUBLIKA, 2026)
This study aims to analyze the institutions, functions, and efficiency of marketing of Fresh Fruit Bunches (FFB) of oil palm by independent smallholders in Dolok Merawan Village, Dolok Merawan District, Serdang Bedagai Regency. The study was conducted in 2026 using quantitative and qualitative descriptive methods. The sample consisted of 33 independent smallholders selected using the simple random sampling method , while the marketing institutions were determined using the snowball sampling technique. The analysis was carried out through the identification of marketing channels, marketing functions, marketing margins, farmer's share , and the ratio of profit to marketing costs. The results showed that there were two marketing channels, namely Channel I (Farmers–Wholesalers/RAM–PKS) used by 12.12% of farmers and Channel II (Farmers–Collectors–Wholesalers/RAM–PKS) used by 87.88% of farmers. The marketing institutions involved included collectors and wholesalers (RAM) who carry out exchange, physical, and facility functions. Channel I has a lower marketing margin (Rp350/kg) compared to Channel II (Rp615/kg), and a higher farmer's share , at 89.55% compared to 81.64%. The profit-to-market cost ratio in Channel I reaches 288.89%, while in Channel II it is 65.63% for collectors and 288.89% for wholesalers. Thus, Channel I is a more efficient marketing channel because it provides a larger share of the price to farmers.